Straightforward synthesis of poly(dimethylsiloxane) phases with immobilized (1R)-3-(perfluoroalkanoyl)camphorate metal complexes and their application in enantioselective complexation gas chromatography - Spallek, Markus Jürgen; Storch, Golo; Trapp, Oliver (European journal of organic chemistry, 2012)
A straightforward synthesis of novel chiral polysiloxane-based metal stationary phases immobilized through a propylenoxy linker (Chirasil-Metal-OC3) to the polymeric backbone is presented. Synthesis was accomplished in six steps with high overall yields starting from commercially available, enantiopure (+)-(1S)-camphorsulfonic acid. Two different approaches towards Chirasil-Metal phases featuring either a propylenoxy or propylenthio linker used for immobilization through hydrosilylation are presented. Furthermore, a new protocol for the fluoroacylation, which is one of the key steps in the synthesis of (1R)-3-(perfluoroalkanoyl)camphorate metal complexes, was developed to improve the isolation and overall yield. The immobilization of (1R,4S)-10-(allyloxy)-3-(heptafluorobutanoyl)camphor - 10-(allyloxy)-hfbc - onto polysiloxanes as well as the incorporation of nickel(II), oxovanadium(IV), europium(III), and lanthanum(III) was characterized by FT ATR IR and NMR spectroscopy. Overall, seven different Chirasil-Metal-OC3 polymers with different separation properties were prepared by metal incorporation and variation of the amount of immobilized (1R,4S)-10-(allyloxy)-3-(heptafluorobutanoyl)camphor (10-allyloxy-hfbc: 3.5, 10.2, and 20.0 %). Their performance in enantioselective complexation gas chromatography was systematically studied and excellent enantioselectivity was found for Chirasil-Nickel-OC3. Separation of 29 small-sized compounds, encompassing, among others, epoxides, substituted alkenes and alkynes as well as alcohols and amides, was achieved with high separation factors α. The synthetic strategy, enantiomer separations and thermal stability (up to 160 °C) demonstrates the versatility of the newly derived Chirasil-Metal-OC3 phases.